2018
DOI: 10.1002/ps.5210
|View full text |Cite
|
Sign up to set email alerts
|

Expression of exogenous dsRNA by Lecanicillium attenuatum enhances its virulence to Dialeurodes citri

Abstract: The results indicate that this method, which uses tens of thousands of hyphae to inject dsRNA to improve the virulence of transgenic fungi, can play a greater role in the prevention and control of pests in the future. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…Dialeurodes citri is a citrus fruit pest which causes soot disease in citrus crops in many locations globally. Currently, only chemical pesticides are used to control D. citri ( Yu et al, 2019 ) . L. attenuatum , an entomopathogenic fungus which causes decreased population size in D. citri , has been explored as a natural alternative to chemical pesticides.…”
Section: Strategies For Production Of Dsrna For Crop Protectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dialeurodes citri is a citrus fruit pest which causes soot disease in citrus crops in many locations globally. Currently, only chemical pesticides are used to control D. citri ( Yu et al, 2019 ) . L. attenuatum , an entomopathogenic fungus which causes decreased population size in D. citri , has been explored as a natural alternative to chemical pesticides.…”
Section: Strategies For Production Of Dsrna For Crop Protectionmentioning
confidence: 99%
“…However, application of the wild type fungi only results in low mortality rates and therefore, it has not been successfully implemented as a biological agent. Different strains of L. attenuatum were developed to produce dsRNA specific to four of the C. citri immune responses, under the control of a constitutive promoter PtrpC ( Yu et al, 2019 ). The fungi produced hpRNA which was subsequently processed by the fungal RNAi machinery into siRNAs.…”
Section: Strategies For Production Of Dsrna For Crop Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beauveria spp. are the most widely used biological control agent against many pests, and Akanthomyces attenuatus has been extensively studied in the control of pests, such as mosquitoes, aphids, whitefly, and thrips (Montalva et al, 2017 ; Yu et al, 2019 ; Amobonye et al, 2020 ; Woo et al, 2020 ). Yang et al ( 2020 ) found that conidial suspensions, as well as crude protein extracts of Beauveria brongniartii isolate SB010 and A. attenuatus isolate SCAUDCL-53, were pathogenic against M. usitatus .…”
Section: Introductionmentioning
confidence: 99%
“…For example, transgenic Metarhizium acridum strains expressing dsRNAs that target genes encoding the α and β subunits of F 1 F 0 ‐ATP synthase in Locusta migratoria displayed a 3.7‐fold increase in virulence (LC 50 ) compared with that of the wild‐type strain (Hu and Xia 2019). Moreover, transgenic Lecanicillium attenuatum expressing dsRNAs that target the genes encoding for prophenoloxidase‐activating factor and lysozymes in Dialeurodes citri exhibited a 3.62‐ and a 2.91‐fold increase in virulence (LC 50 ) compared with that of the wild‐type strain, respectively (Yu et al ., 2019). These studies demonstrated that transgenic fungi expressing dsRNAs specific to insect immune response‐associated genes serve as potential vectors to facilitate the application of dsRNAs for pest control in the field.…”
Section: Introductionmentioning
confidence: 99%